Plan de marketing internacional para la empresa Mushuk Moda Cantón Otavalo. - Guerra, Jaime A. (2019)
The present work carried out in the canton of Otavalo, province of Imbabura, seeks to solve the problem faced by micro-enterprises dedicated to the textile sector. Therefore, as a possible solution to the lack of trade and studying the production capacity of the company Mushukmoda, it was found that the hand-embroidered casual blouses have a great reception among international tourists who visit the city of Otavalo. In this way, it is proposed as a possible solution to commercialize internationally the hand-embroidered casual blouses of the Mushukmoda company through an international marketing plan. The Plan contains as a first point to establish the mission, vision and values on which the company will base itself, as well as the benefits of the product as well as the cost and international sales price it will achieve. While the tools that will be used to promote handembroidered casual blouses will all be digital, for these purposes a web page, an online store and accounts on social networks such as Facebook and Instagram where it is promoted, means by the which will help to attract customers and have an efficient communication regardless of any distance. Finally, it is forecast that sales will grow 6.5% for the first year in which the Mushukmoda company begins to commercialize internationally, the market that is aimed at is the North American one